Wellness and Health Tourism in Thailand: a Chinese Visitors' Perceptions of Transcultural Nursing - Panyanak, Lalitphan; Chaisaengpratheep, Nattapong; Masuk, Pichanika (Community and Social Development Journal, 2022)
The researchers conducted a quantitative study in Thailand with 520 Chinese visitors who had used Thailand's health and medical services. The precise number is unknown, but there are numerous. The effect size f = 0.25, error probability = 0.01, and power of test (1 -) = 0.99 were calculated using G*Power (Faul et al., 2013). To investigate transcultural nursing perceptions during health and medical tourism. A five-point Likert scale was used to score 32 observed variables in an accidental sampling. Exploratory Factor Analysis (EFA) was used to analyse the data and determine how visitors perceived transcultural nursing. The outcomes demonstrated that the factors influencing visitors’ perception, which consisted of five factors and 31 observed variables, had a cumulative variance of 73.892%. Visitors' impressions of people who use wellness and healthcare services were influenced by factor 1, sanitation issues, and Thai medical standards, which had the highest percentage of variance. The remaining four criteria included psychological skills (10.444%), ancillary services (14.934%), nursing and biological variation (13.552%), and communication and privacy (16.634%), respectively. These factors can be credited to the benefits of research in identifying marketing tactics that increase awareness and offer top-notch service, enhancing competitive advantages by luring new customers and satisfying the wants of returning ones.